EFFECT OF FREE AND BOUND FLAVONOIDS FROM WRIGHTIA TINCTORIA (ROXB) R. BR. LEAVES ON SKIN PATHOGENS - T. SENTHIL KUMAR; D. VENKAPPAYYA; VILAMBI N.R.K. REDDY; R. MANAVALAN (International Journal of Pharma and Bio Sciences, 2013)
The causative agents of skin infection are bacteria, fungi and in specific dermatophytes. Many infectious diseases have been treated with plant extracts. The free and bound flavonoids fractions of Wrightia tinctoria (Roxb) R.Br. (Apocynaceae), leaves were tested against 10 bacterial, 3 fungal and 4 dermatophytic strains affecting the skin using disc diffusion and broth micro dilution method. The free flavonoidal extract showed maximum activity against Bacillus subtilis (gram positive), Proteus vulgaris (gram negative), Candida albicans (fungus) and Trichophyton rubrum (dermatophyte). The bound flavonoidal extract showed maximum activity against Staphylococcus aureus (gram positive), Escherichia coli (gram negative), Candida albicans (fungus) and Epidermophyton floccosum (dermatophytes) among the various tested organisms. The bounded flavonoidal extract (activity index 0.58) had strong activity against dermatophytes. This provides a lead that, flavonoidal extract could be used for direct incorporation into formulations for effective treatment and a scientific rationale for the traditional use of Wrightia tinctoria in treating skin infections.